2016
DOI: 10.1103/physreva.93.022703
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chaos in ultracold collisions betweenYb(1S0)andYb(3P2)

Abstract: We calculate and analyze Feshbach resonance spectra for ultracold Yb( 1 S0) + Yb( 3 P2) collisions as a function of an interatomic potential scaling factor λ and external magnetic field. We show that, at zero field, the resonances are distributed randomly in λ, but that signatures of quantum chaos emerge as a field is applied. The random zero-field distribution arises from superposition of structured spectra associated with individual total angular momenta. In addition, we show that the resonances in magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…A re-analysis of the erbium results [30] showed that the deviations from chaotic predictions might arise because some narrow resonances are not observed in the experiment. A comparable degree of chaos has recently been found in coupled-channel calculations on the remarkably simple system Yb( 1 S)+Yb( 3 P) [31]. However, similar calculations on Li+Er found statistics consistent with a random but non-chaotic level distribution [32].…”
Section: Introductionsupporting
confidence: 73%
“…A re-analysis of the erbium results [30] showed that the deviations from chaotic predictions might arise because some narrow resonances are not observed in the experiment. A comparable degree of chaos has recently been found in coupled-channel calculations on the remarkably simple system Yb( 1 S)+Yb( 3 P) [31]. However, similar calculations on Li+Er found statistics consistent with a random but non-chaotic level distribution [32].…”
Section: Introductionsupporting
confidence: 73%
“…6(a) and 6(b) raise a question of whether the investigated systems exhibit a quantum chaotic behavior. For ultracold collisions of Dy and Er atoms it was measured [16,25] and theoretically confirmed [16,44,[64][65][66][67] that the interplay of anisotropic electronic and dipolar interactions leads to the chaotic spectra of Feshbach resonances being the signature of the level repulsion following the predictions of the Gaussian Orthogonal Ensemble of random matrices [68]. Similar results were predicted for atom-molecule collisions [69][70][71].…”
Section: Numerical Results and Discussionsupporting
confidence: 65%
“…In our analysis of the chaotic behaviour of resonance spacings we take into account the slow variation of resonance density by following the standard 'unfolding' procedure [28,73]. resonance every 3G.…”
Section: Resonance Statistics and Evidence Of Quantum Chaosmentioning
confidence: 99%
“…Thus, η becomes a quantitative measure of chaotic behaviour where η close to zero indicates a lack of chaos, while η near unity shows strong level repulsion. Following Greenet al [28] we calculate the Brody parameter η through max-likelihood estimation: η can be found by maximizing the log-likelihood ( )…”
Section: Resonance Statistics and Evidence Of Quantum Chaosmentioning
confidence: 99%
See 1 more Smart Citation